-4(5y-5)-y=-3(y-3)

Simple and best practice solution for -4(5y-5)-y=-3(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5y-5)-y=-3(y-3) equation:



-4(5y-5)-y=-3(y-3)
We move all terms to the left:
-4(5y-5)-y-(-3(y-3))=0
We add all the numbers together, and all the variables
-1y-4(5y-5)-(-3(y-3))=0
We multiply parentheses
-1y-20y-(-3(y-3))+20=0
We calculate terms in parentheses: -(-3(y-3)), so:
-3(y-3)
We multiply parentheses
-3y+9
Back to the equation:
-(-3y+9)
We add all the numbers together, and all the variables
-21y-(-3y+9)+20=0
We get rid of parentheses
-21y+3y-9+20=0
We add all the numbers together, and all the variables
-18y+11=0
We move all terms containing y to the left, all other terms to the right
-18y=-11
y=-11/-18
y=11/18

See similar equations:

| (2+x)/3=(9+x)/3 | | 4=y/5-11 | | 4/m+3/8=67/8 | | 2+x/3=9+x/3 | | 50=28.1+.15a | | 2+y/2=-10 | | 2+x/3=9+x3/5 | | s+1=2s | | 13x+2=8(x+1)+7 | | -4y(5y-5)-y=-3(y-3) | | (2+x/3)+3= 9+x3/5 | | 5y-9=38 | | 5g+7=-3g+1 | | 5g+7=- | | 10y-6y-5=39.72 | | 1/z+4=5/2z-8 | | F(x)=x33-4x | | 83-6x=3x+11 | | X-2+x+90=180 | | -t=t(9-10) | | 64-4(-2x-9)=0 | | 4x-5=8x-3 | | 4x-5=8x-8 | | -t=5(9-10) | | 21+5x=3x+11 | | -14v=252 | | 4(x-1)/10=2(x+2)/8 | | (4(x-2))/(x-3)+(3/x)=(-3/x(x-3)) | | 5(r+9)-2(1+-r)=1 | | 3x+8=5x-12* | | 4(2x+9)=-37+65 | | 2x-18=-12* |

Equations solver categories